Situational efficacy of top Croatian senior beach volleyball players - Simac, M.; Grgantov, Z.; Milic, M. (Acta Kinesiologica, 2017)
The aim of this study was to determine the significance of differences between successful and less successful beach volleyball players in the quality of performance in 6 basic technical and tactical elements, i.e., phases of the game: service, serve reception, setting for the spike, spike, block and field defense. To collect data, 35 matches played in two tournaments of senior men`s Croatian Club Championship in beach volleyball were analysed from video recordings. The quality of performance of technical and tactical elements was estimated on a scale from 1 (a mistake in performance) to 4 (ideal performance). Based on the collected data, coefficients of efficacy were calculated for the analysed phases of the game. The lowest coefficient values were found in efficacy of the service (2.21) and block (2.62) phases, and the highest in the phases of the setting for the spike (3.49) and serve reception (3.28). Situational efficacy of volleyball players was estimated based on team placement in competition and the status of players within a team. By the criterion of situational efficacy, players were divided into two groups: less successful and successful players. By analysis of variance, it was found that successful beach volleyball players had significantly higher coefficients of efficacy in comparison to the less successful players in all 6 analysed phases of the game. The most pronounced differences were found in the phase of setting for the spike, serve reception and spike. The obtained results point to the importance of quality performance of all phases of the game in beach volleyball, and especially those that are performed in the attack complex.